Updated estimates of carbon accumulation rates in coastal marsh sediments - X. Ouyang; S. Y. Lee (Biogeosciences, 2014)
Studies on carbon stock in salt marsh sediments have increased since the review by Chmura et al. (2003). However, uncertainties exist in estimating global carbon storage in these vulnerable coastal habitats, thus hindering the assessment of their importance. Combining direct data and indirect estimation, this study compiled studies involving 143 sites across the Southern and Northern hemispheres, and provides an updated estimate of the global average carbon accumulation rate (CAR) at 244.7 g C m−2 yr−1 in salt marsh sediments. Based on region-specific CAR and estimates of salt marsh area in various geographic regions between 40° S to 69.7° N, total CAR in global salt marsh sediments is estimated at ~10.2 Tg C yr−1. Latitude, tidal range and elevation appear to be important drivers for CAR of salt marsh sediments, with considerable variation among different biogeographic regions. The data indicate that while the capacity for carbon sequestration by salt marsh sediments ranked the first amongst coastal wetland and forested terrestrial ecosystems, their carbon budget was the smallest due to their limited and declining global areal extent. However, some uncertainties remain for our global estimate owing to limited data availability.